Efektivitas Pijat Endorphine Terhadap Kecemasan Pada Masa Nifas - Melicha Kristine Simanjuntak; Sestu Iriami Mintaningtyas; Priscilla Jessica Pihahey; Mirna Wigunarti; Deasy Erawati (Jurusan Kebidanan Poltekkes Kemenkes Mamuju, 2026)
Anxiety is a common emotional reaction experienced by postpartum mothers due to physiological, psychological, and social changes that occur after childbirth. If not properly managed, this anxiety can negatively affect the mother’s recovery process, breast milk production, and the bonding between mother and baby. One of the non-pharmacological approaches increasingly developed to reduce anxiety is the administration of endorphin massage therapy. This therapy works by stimulating the release of endorphin hormones, which promote relaxation, reduce muscle tension, and increase comfort without the side effects associated with pharmacological therapy. This study aims to determine the effectiveness of endorphin massage in reducing anxiety levels among postpartum mothers. The research used a quasi-experimental design with a pretest–posttest without control group approach. The study was conducted at Manokwari Regional Hospital, West Papua Provincial Hospital, and Pelita Kasih Clinic, involving 30 postpartum mothers as respondents from July to September 2025. Data were collected using the Perinatal Anxiety Screening Scale (PASS) questionnaire and analyzed using the Friedman test. Before receiving endorphin massage, most respondents experienced moderate (66.7%) and severe anxiety (26.7%). After the intervention, the majority showed a reduction in anxiety levels to the non-anxious (60%) and mild anxiety (26.7%) categories. The Friedman test result showed a p-value < 0.001, indicating a statistically significant difference between anxiety levels before and after the intervention. The study concludes that endorphin massage is significantly effective in reducing anxiety levels among postpartum mothers. This therapy can serve as a safe, affordable, and easily applicable non-pharmacological intervention in midwifery care to support maternal mental health after childbirth.